The Implementation of Merrill’s Principles of Instruction in English Productive Skills - Andi Tenri Ampa, Muhammad Basri D. and Sulfasyah (International Journal of Advanced Science and Technology, 2020)
Productive skills which include the English speaking and writing skills are very essential to increase in learning English. Therefore, the research attempted to implement the Merrill’s principle of instruction to enhance English productive skills. The study had used a pretest-posttest control design in which the experimental group was treated with the phases of Merrill’s principle of instruction and the control group was treated with the conventional way. The number of samples was 60 students taken from a number of populations (300 students) and placed into two groups. For the attempt mentioned, the statistical technique (SPSS) was utilised to process the data that had been prepared. The research findings revealed that applying any instructional design model with the respective treatment improved the English productive skills effectively. However, the inference of the findings asserted that the mean score of the participants treated with the phases of Merrill’s principle of instruction performed better than those who were treated with the conventional way.